Análise socioambiental da microbacia do rio Caiçá no perímetro urbano de Simão Dias-SE - Fontes, Andréia Reis (2016)
Throughout history, cities more economically prospered and developed civilizations were those that had considerable availability of water resources and were surrounded by major rivers. However, present day reveals that many times this has become an inexhaustible source of environmental problems. In this perspective, Simão Dias is an example of this reality. The simãodiense urban area, especially the three housing developments located along the Caiçá river, is responsible for the domestic sewage discharge and anthropogenic pressures on water courses. Based on this, the present study aimed to carry out an environmental analysis of the watershed Caiçá River within the city limits of Simão Dias and its effects on the local quality of life. In addition, aimed to identify the anthropogenic pressures in the study area; evaluate the water quality in the urban stretch of the watershed; analyzing the use of water resources at the local level; identify the socioeconomic and environmental conditions of the community and how these have an impact on the watershed. The methodological research framework encompasses the hypothetical-deductive method. The nature of the study has a qualitative and quantitative approach and survey of socioeconomic data was carried out from primary and secondary data, in addition to satellite images allowance and elaborate thematic maps. Among the environmental components, vegetation assessment was performed by means of georeferencing and according to the cartographic base of the Digital Atlas About Water Resources of the State of Sergipe / SEPLAN / SRH-2014. Land use was through mapping done from RapidEye satellite imagery (RE2 and RE4). Water analysis was based on Standard Methods for the Examination of Water and Wastewarter (APHA, 2005), in which the parameters could be compared with CONAMA 357/2005. The results showed that the anthropogenic pressures (urbanization, the abattoir presence, degradation of riparian vegetation, inappropriate land use, and disposal of domestic tributaries), exert negative influence on the Caiçá river, compromising the quality of the water body, represented by the index water quality, which classified the resource as bad, showing therefore the need for effective action with regard to water management at the local level.